Allotanaupodidae, a new family of early derivative Parasitengona (Acari: Prostigmata) - Zhang, Zhi-Qiang; Fan, Qing-Hai (Zootaxa, 2007)
A new family of early derivative Parasitengona (Acari: Prostigmata), Allotanaupodidae fam. nov., is described from New Zealand based on adults and deutonymphs of two new genera and five new species and a new superfamily Allotanaupodoidea is erected to accommodate it. The new family is characterized by the absence of prodorsal trichobothria and sensory areas, the presence of one or two pairs of plates with multiple setae on C to PS rows of dorsal hysterosoma, the presence of only two pairs of genital acetabula in adults, and short, distally inserted palptarsus on the palptibia. The family consists of two subfamilies (Allotanaupodinae subfam. nov. and Paratanaupodinae subfam. nov.), with the former endemic to New Zealand. Allotanaupodinae subfam. nov. has a single genus, Allotanaupodus gen. nov., which is represented by three new species from New Zealand: Allotanaupodus williamsi sp. nov. (type species) from Kawau I., Auckland, Allotanaupodus orete sp. nov. from Orete Forest, Te Puia Hut and Allotanaupodus winksi sp. nov. from Mt. Messenger, Taranaki. The eyeless Paratanaupodinae subfam. nov. consists of two genera: Nanotanaupodus gen. nov. and Paratanaupodus Andre & Lelievre-Farjon, 1960. The type genus Paratanaupodus Andre & Lelievre-Farjon, 1960 was previously placed in the Tanaupodidae and is represented by a single species, Paratanaupodus insensus André & Lelievre-Farjon, 1960, from South America. Nanotanaupodus gen. nov. is represented by two new species from New Zealand: Nanotanaupodus andrei sp. nov. (type species) from Waituhi Saddle and Nanotanaupodus gracehallae sp. nov. from Orete Forest, Te Puia Hut. A key to superfamilies of terrestrial Parasitengona (post-larval stages) is provided, along with keys to subfamilies, genera and species of the new family.